Inhibitor of apoptosis-stimulating protein of p53 (iASPP) is required for neuronal survival after axonal injury. - Ariel M Wilson; Vince A Chiodo; Sanford L Boye; Nicholas C Brecha; William W Hauswirth; Adriana Di Polo (PLoS ONE)
The transcription factor p53 mediates the apoptosis of post-mitotic neurons exposed to a wide range of stress stimuli. The apoptotic activity of p53 is tightly regulated by the apoptosis-stimulating proteins of p53 (ASPP) family members: ASPP1, ASPP2 and iASPP. We previously showed that the pro-apoptotic members ASPP1 and ASPP2 contribute to p53-dependent death of retinal ganglion cells (RGCs). However, the role of the p53 inhibitor iASPP in the central nervous system (CNS) remains to be elucidated. To address this, we asked whether iASPP contributes to the survival of RGCs in an in vivo model of acute optic nerve damage. We demonstrate that iASPP is expressed by injured RGCs and that iASPP phosphorylation at serine residues, which increase iASPP affinity towards p53, is significantly reduced following axotomy. We show that short interference RNA (siRNA)-induced iASPP knockdown exacerbates RGC death, whereas adeno-associated virus (AAV)-mediated iASPP expression promotes RGC survival. Importantly, our data also demonstrate that increasing iASPP expression in RGCs downregulates p53 activity and blocks the expression of pro-apoptotic targets PUMA and Fas/CD95. This study demonstrates a novel role for iASPP in the survival of RGCs, and provides further evidence of the importance of the ASPP family in the regulation of neuronal loss after axonal injury.